An Investigation on the Dynamic Response of Cable Stayed Bridge with Consideration of Three-Axle Vehicle Braking Effects. (11th June 2017) - Nguyen, Xuan-Toan; Tran, Van-Duc; Hoang, Nhat-Duc
Abstract : The cable-stayed bridge (CSB) is often used to span over the large rivers on the highway with a high-level navigational clearance; however, CSB is very sensitive to live load. Most of the previous studies on vibration analysis of CSB that focus on complex traffic loading and vehicle dynamic interaction as well as on the bridge deck do not consider braking effects thoroughly. In this paper, the finite element method (FEM) is used to investigate the dynamic response of CSB due to a three-axle vehicle considering braking effects. Vertical reaction forces of axles that change with time make bending vibration of the bridge deck increase significantly. The braking in a span is able to create response in other spans, towers, and cables. In addition, the impact factors are investigated on both FEM and experiment with a case study of Pho Nam bridge (Danang city, Central Vietnam). The results of this study provide an improved understanding of the CSB dynamic behaviors, and they can be used as useful references for bridge codes by practicing engineers.